Soil conditions under natural logged-over and secondary stands of tropical seasonal forest in Thailand - Yarwudhi, C.; Kobayashi, S.; Tanaka, N.; Suksawang, S. (Center for International Forestry Research, 2001)
Soil samples from permanent sample plots of natural mixed deciduous, logged-over mixed deciduous and the secondary stands in the tropical seasonal forest were analysed for physical and chemical properties. Bulk density and soil hardness of A-horizon in the natural stand were slightly higher than in logged-over and the secondary stands with average bulk densities 1.2, 1.1 and 1.0 g cm-3 and soil hardness 17, 16 and 15 respectively. Secondary stands had slightly higher B-horizon hardness than the natural and the logged-over stands. Total pore value (volumetric %) of the secondary stand was higher than the logged-over and the natural stands with the average of 48, 45 and 42 % respectively. Secondary stand fine pore percentage was also higher than that of the natural and the logged-over stands with the average of 29, 25 and 24 % respectively. Soil permeability was highest in the secondary stand with an average of 122 ml minute-1 while in logged-over and natural stands it was are 116 and 45 ml minute-1 respectively. Soil organic matter in the secondary, natural and logged-over stands was 7.3, 6.0 and 5.0% respectively. There is much variation in P, K, Ca and Mg content in all stands. The maximum content of P in the natural, logged-over and secondary stands are 35, 57 and 26 ppm. respectively, while the minimum P content was 4, 4 and 2 ppm respectively. Average P contents were in the range 9-12 ppm. The average K content in natural, logged-over and secondary stands was 188, 230 and 555 ppm, average Ca was 963, 938 and 1109 ppm, and average Mg 289, 528 and 413 ppm respectively. It is concluded that there is little difference in most soil properties in these stands, except soil permeability in the natural stand is lower than in the other two stands. This may be the effect of high soil bulk density and the low coarse pore volumetric percentage.